Volunteering and education (Journal of Parents and Teachers, 2023)
Undoubtedly, solidarity is one of the values that are becoming more relevant in many areas due to its importance. For this reason, the article proposes an activity related to volunteering to be carried out in 3 sessions in the classroom. In addition, it indicates 7 steps to become people who show a little more solidarity with others.
Keywords: solidarity; volunteering; education